LncRNA H19 ameliorates myocardial infarction‐induced myocardial injury and maladaptive cardiac remodelling by regulating KDM3A - Zhang, Bo‐fang (J Cell Mol Med, 2019)
Myocardial infarction (MI) remains the leading cause of morbidity and mortality worldwide, and novel therapeutic targets still need to be investigated to alleviate myocardial injury and the ensuing maladaptive cardiac remodelling. Accumulating studies have indicated that lncRNA H19 might exert a crucial regulatory effect on cardiovascular disease. In this study, we aimed to explore the biological function and molecular mechanism of H19 in MI. To investigate the biological functions of H19, miRNA‐22‐3p and KDM3A, gain‐ and loss‐of‐function experiments were performed. In addition, bioinformatics analysis, dual‐luciferase reporter assays, RNA immunoprecipitation (RIP) assays, RNA pull‐down assays, quantitative RT‐PCR and Western blot analyses as well as rescue experiments were conducted to reveal an underlying competitive endogenous RNA (ceRNA) mechanism. We found that H19 was significantly down‐regulated after MI. Functionally, enforced H19 expression dramatically reduced infarct size, improved cardiac performance and alleviated cardiac fibrosis by mitigating myocardial apoptosis and decreasing inflammation. However, H19 knockdown resulted in the opposite effects. Bioinformatics analysis and dual‐luciferase assays revealed that, mechanistically, miR‐22‐3p was a direct target of H19, which was also confirmed by RIP and RNA pull‐down assays in primary cardiomyocytes. In addition, bioinformatics analysis and dual‐luciferase reporter assays also demonstrated that miRNA‐22‐3p directly targeted the KDM3A gene. Moreover, subsequent rescue experiments further verified that H19 regulated the expression of KDM3A to ameliorate MI‐induced myocardial injury in a miR‐22‐3p‐dependent manner. The present study revealed the critical role of the lncRNAH19/miR‐22‐3p/KDM3A pathway in MI. These findings suggest that H19 may act as a potential biomarker and therapeutic target for MI.